Cultural Awareness in Nuclear Security Programs: A Critical Link - Al-Sharif Nasser Bin Nasser; Jasmine Auda; Katherine Bachner (International Journal of Nuclear Security, 2016)
Nuclear security programs that offer training and capacity building opportunities to practitioners working in nuclear facilities play a central role in strengthening the global nuclear security architecture. There is often a significant divide, however, between both the development of these programs and their implementation, and between the programs’ intended and actual outcomes. As this article will argue, this disconnect can often be attributed to an absence of cultural awareness and an inability for internationally-designed programs to effectively resonate with local audiences. Accordingly, the importance of the role of cultural awareness in implementing nuclear security programs will be assessed, and its applications in the Jordanian context will be presented.
Keywords: Nuclear Security Culture; Nuclear Security; Middle East